2020
DOI: 10.1111/opo.12709
|View full text |Cite
|
Sign up to set email alerts
|

Experiences following cataract surgery – patient perspectives

Abstract: Purpose Most patients report being highly satisfied with the outcome of cataract surgery but there are variable reports regarding the impact of cataract surgery on some real‐world activities, such as fall rates. We hypothesised that adaptations to changed refractive correction and visual function may cause difficulties in undertaking everyday activities for some patients and used a series of focus groups to explore this issue. Method Qualitative methods were used to explore patients’ experiences of their visio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(31 citation statements)
references
References 27 publications
(36 reference statements)
0
31
0
Order By: Relevance
“…20 Despite this, a recent focus group study (n = 26) found 27% of patients had discussion regarding their target refraction or were not given sufficient time or information to make an informed choice, and therefore deferred to the ophthalmologist's recommendation. 11 This study aimed to investigate if clinicians did discuss target refraction with their patients. We found both optometrists and ophthalmologists had differing views of when target refraction should first be discussed with the patient.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…20 Despite this, a recent focus group study (n = 26) found 27% of patients had discussion regarding their target refraction or were not given sufficient time or information to make an informed choice, and therefore deferred to the ophthalmologist's recommendation. 11 This study aimed to investigate if clinicians did discuss target refraction with their patients. We found both optometrists and ophthalmologists had differing views of when target refraction should first be discussed with the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Target refraction discussions are vital to ensure patient satisfaction post‐operatively. Current advice from the NHS states, “Providers must ensure that patients have sufficient time to consider these complex issues, and decisions such as post‐operative target refraction should be determined and agreed with the patient well in advance of the scheduled surgery date.” 20 Despite this, a recent focus group study ( n = 26) found 27% of patients had no discussion regarding their target refraction or were not given sufficient time or information to make an informed choice, and therefore deferred to the ophthalmologist's recommendation 11 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations